Resilience in the Aftermath of Childhood Abuse? Changes in Religiosity and Adulthood Psychological Distress - Upenieks, Laura (Journal of religion and health, 2021)
Of all the forms of adversity experienced during childhood, childhood abuse is known to have the largest impacts on mental health. Yet, we have a limited understanding of factors that may cushion the blow of these early insults, and it remains unclear whether stability or increases/decreases in religiosity facilitate or hinder the ability of religion/spirituality to act as a buffer. Using two waves of MIDUS data, results suggest that increases in positive religious coping (seeking comfort through religion/spirituality) during adulthood buffer the association between childhood physical and emotional abuse on psychological distress, while decreases in religious comfort exacerbate it. Religious attendance had no discernible buffering effect. Taken together, results show that the stress-moderating effects of religion depend on changes in religious coping processes over the life course.